Ethnic inequities in 6–8 week baby check coverage in England 2006– 2021: a cohort study using the Clinical Practice Research Datalink - Zhang, CX; Quigley, MA; Bankhead, C; Kwok, CH; Parekh, N; Carson, C (Royal College of General Practitioners, 2024)
Background: Inequities in the coverage of 6-8 week maternal checks, health visitor reviews and infant vaccinations have been reported in England. Ethnic inequities in 6-8 week baby checks have not been studied nationally. Aim: To examine the effect of maternal ethnicity on 6-8 week baby check coverage in England 2006-2021. Design and Setting: Cohort study using electronic health records. Methods: We calculated baby check coverage in 16 ethnic groups, by year and region, and risk ratios using modified Poisson regression. We calculated coverage and timing of baby checks in relation to maternal checks and infant vaccinations by ethnic group. Results: Ethnic inequities in 6-8 week baby check coverage in England varied by year and region. Coverage increased 2006-07 to 2015-16, then stabilised to 80-90% for most groups. Coverage was lowest for Bangladeshi and Pakistani groups 2006-07 to 2011-12. In the West Midlands, coverage was lowest at 59% for four groups: Bangladeshi, Caribbean, African, and Any other Black, African or Caribbean background. In the North West, coverage was lowest for Bangladeshi (65%) and Pakistani (69%) groups. These patterns remained after adjusting for other factors, and persisted over time. Coverage was highest in those whose mothers received a maternal check and those who received at least one dose of 8 week infant vaccinations. Conclusions: Coordinated action at the level of integrated commissioning boards, primary care networks and GP practices is required to better understand the reasons behind these inequities and redress the persistent disparities in 6-8 week baby check coverage.